Процессы восстановления водного баланса спортсмена - Абдуллаєв, Алтай Карам-Огли; Абдуллаев, Алтай Карам-Оглы; Abdullaev, Altai; Ребар, И. В.; Нестеров, Олексій Сергійович; Нестеров, Алексей Сергеевич; Nesterov, Oleksii (ЧНПУ, 2015)
RU: В данной статье рассмотрена проблема, актуальность, задачи процессов восстановления водного баланса в организме спортсмена. Также проанализирована специальная литература. Рассмотрено влияние водного баланса на состояние здоровья спортсмена. Указаны роль воды в организме и состояние воды. Полностью раскрыто определение термина "обезвоживание". Рассмотрено процентное соотношение воды с другими веществами организма. Дано рекомендации правильного регулирования водного баланса во время тренировочных занятий. EN: This article describes the problem, the relevance and the problem of recovery of the water balance in the body of an athlete. Water is the most important nutrient of all the body needs. It is necessary for regulating body temperature, skin moisturizing and the delivery of oxygen and other nutrients to the cells. Consumption of a required amount of water is an important condition for optimum physical performance and endurance. Normal water balance is a necessary condition for the maintenance of physical performance of an athlete, for the normal functioning of the brain during exercises and for the recovery after injury. The negative water balance, or dehydration, can disrupt the function of the cardiovascular system and temperature regulation and is a threat of injury and even death of the athlete. Proper water balance is one of the most important components of a healthy lifestyle. Water is involved in solubilizing of many compounds, which increases the speed of many reactions in transport of materials in the assimilation of food in the gastrointestinal tract, in the delivery of nutrients to the cells of the organism and the selection of the body metabolic products in the urine and sweat, in the maintaining the structure and function of cell organelles in biochemical reactions of metabolism of carbohydrates, lipids, proteins, ATP, in the maintenance of acid-base balance of the medium of the body, in the creating an osmotic pressure dependent concentration of organic and inorganic substances dissolved in it, in the protection of the mechanical friction surfaces, in the processes of thermoregulation of the organism. Thus, the water regulates the temperature and body weight, brings the nutrients to the cells, eliminates decomposition products from the body and carries a plurality of different functions. Almost all the vital processes in the body take place with the participation of water. Our prospects for further research is in propaganda not only among athletes but also among the other people about the benefits of water, because water promotes fat burning, the normal functioning of the kidneys, metabolic processes, high efficiency, etc. The special literature is also analyzed during our research. The in fluence of the water balance on the health of an athlete is reviewed. The role of water in a body and the state of water are specified. The definition of "dehydration" is fully disclosed. The percentage of water with the substances of the body is examined. Recommendations are given towards the proper regulation of the water balance during the training exercises.
Recovery process of athlete’s water balance
Keywords: вода; водный баланс; обезвоживание; метаболизм; гидратация; спортсмен; физические нагрузки; гидролиз; water; waterbalance; dehydration; metabolism; hydration; theathlete; exercise; hydrolysis